Hadith #2409 - Sunan Abi Dawud - Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; Uqba bin Mukaram bin Aflah al-''Ami عقبة بن مكرم (Sunan Abi Dawud)
We went out along with the Messenger of Allah (ﷺ) for some battle in intense heat, so much so that one of us placed his hand on his head, or placed his palm on his head, due to intense heat, No one of us fasted except the Messenger of Allah (ﷺ) and ‘Abd Allah b. Rawahah.
Grade: Sahih

Hadith #2617 - Sunan Abi Dawud - Anas ibn Malik; Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; Sulaiman bin al-Mughira al-Qaysy سليمان بن المغيرة القيسي مولاهم; Thabit bin Aslam Albanani ثابت بن أسلم البناني (Sunan Abi Dawud)
Abu Mishar was told about Ubna. He said “We know it better. This is Yubna of Palestine.
Grade: Sahih

Hadith #2653 - Sunan Abi Dawud - Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; Ikrama bin 'Ammar عكرمة بن عمار العجلي أبو عمار اليمامي (Sunan Abi Dawud)
Ibn Salamah bin Al Akwa’ repoted on the authority of his father. A spy of the polytheists came to the Prophet(ﷺ) when he was on a journey. He sat near his Companions and then slipped away. The Prophet(ﷺ) said “look for him and kill him”. He said “I raced to him and killed him. I took his belongings which he (the Prophet) gave me.
Grade: Sahih

Hadith #2696 - Sunan Abi Dawud - Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; Ikrama عكرمة (Sunan Abi Dawud)
Ali separated between a slave-girl and her child. The Prophet (ﷺ) prohibited it and made the sale transactions withdrawn. Abu Dawud said: The narrator Maimun (b. Abi Shaib) did not meet ‘Ali. He (Maimun) was killed in the battle of Jamajim in 83 A.H. Abu Dawud said: The battle of Harrah took place in 63 A.H., and Ibn al-Zubair was killed in 73 A.H.
Grade: Hasan

Hadith #2751 - Sunan Abi Dawud - Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; Ikrama عكرمة (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: Muslims are equal in respect of blood. The lowest of them is entitled to give protection on behalf of them, and the one residing far away may give protection on behalf of them. They are like one hand over against all those who are outside the community. Those who have quick mounts should return to those who have slow mounts, and those who got out along with a detachment (should return) to those who are stationed. A believer shall not be killed for an unbeliever
Grade: Hasan Sahih

Hadith #2857 - Sunan Abi Dawud - Abdur Rahman bin 'Abdullah bin Dinar عبد الرحمن بن عبد الله بن دينار; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; Uthman bin Muhammad; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
There was a bedouin called AbuTha’labah. He said: Messenger of Allah, I have trained dogs, so tell me your opinion about (eating) the animal they hunt. The Prophet (ﷺ) said: If you have trained dogs, then eat what they catch for you. He asked: Whether it is slaughtered or not? He replied: Yes. He asked: Does it apply even if it eats any of it? He replied: Even if it eats any of it. He again asked: Messenger of Allah, tell me your opinion about my bow (i.e. the game hunted by arrow). He said:
Grade: Hasan

Hadith #3294 - Sunan Abi Dawud - Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; ibn Abbas; Karayb bin Abi Muslim كريب بن أبي مسلم الهاشمي; Muhammad bin 'Abdur Rahman bin 'Ubaid محمد بن عبد الرحمن بن عبيد القرشي; Sharayk bin 'Abdullah شريك بن عبد الله النخعي (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Abu Sa’id al-Ru’aini with the same chain as narrated by Yahya (b. Sa’id) and to the same effect.
Grade: Da'if

Hadith #3425 - Sunan Abi Dawud - Harun bin 'Abdullah al-Hamal هارون بن عبد الله بن مروان الحمال; Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; Ikrama عكرمة (Sunan Abi Dawud)
That the Messenger of Allah (ﷺ) forbade earnings of slave-girls.
Grade: Sahih

Hadith #4023 - Sunan Abi Dawud - Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; Ishaq bin Sa'id bin 'Amr bin Sa'id إسحاق بن سعيد بن عمرو بن سعيد; Sa'id bin 'Amr bin Sa'id bin al-Aas سعيد بن عمرو بن سعيد بن العاص; Umm Khalid bin Khalid ibn Sa'id (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone eats food and then says: “Praise be to Allah Who has fed me with this food and provided me with it through no might and power on my part,” he will be forgiven his former and later sins. If anyone puts on a garment and says: “Praise be to Allah Who has clothed me with this and provided me with it through no might and power on my part,” he will be forgiven his former and later sins.
Grade: Hasan

Hadith #4030 - Sunan Abi Dawud - Abdur Rahman bin Thabit عبد الرحمن بن ثابت بن ثوبان العنسي; Abu al-Mnyb al-Jrshy أبو المنيب الجرشي; Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; Hsan bin Atyh al-Mharby حسان بن عطية المحاربي مولاهم; ibn Umar; Uthman bin Muhammad (Sunan Abi Dawud)
Garment of disgrace.
Grade: Hasan

Hadith #4292 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abdur Rahman bin Thabit عبد الرحمن بن ثابت بن ثوبان العنسي; Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; Jubayr bin Nufayr al-Hadrami; Makhul al-Shami/al-Damashiqi مكحول الشامي; Malik bin Yakhamar مالك بن يخامر; Mu'adh ibn Jabal (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: you will make a secure peace with the Byzantines, then you and they will fight an enemy behind you, and you will be victorious, take booty, and be safe. You will then return and alight in a meadow with mounds and one of the Christians will raise the cross and say: The cross has conquered. One of the Muslims will become angry and smash it, and the Byzantines will act treacherously and prepare for the battle.
Grade: Sahih

Hadith #4955 - Sunan Abi Dawud - Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Amir al-Sha'bi عامر الشعبي; Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; Masrouq bin al-Ajda' مسروق بن الأجدع; Mujalid bin Sa'id bin 'Umayr مجالد بن سعيد الهمداني (Sunan Abi Dawud)
When Hani went with his people in a deputation to the Messenger of Allah (ﷺ), he heard them calling him by his kunyah (surname), AbulHakam. So the Messenger of Allah (ﷺ) called him and said: Allah is the judge (al-Hakam), and to Him judgment belongs. Why are you given the kunyah AbulHakam? He replied: When my people disagree about a matter, they come to me, and I decide between them, and both parties are satisfied with my decision. He said: How good this is! What children have you? He replie
Grade: Sahih

Hadith #5096 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin Salah al-Masri أحمد بن صالح المصري; Amr bin al-Harith bin Ya'qub عمرو بن الحارث; Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; Sulayman ibn Yasar سليمان بن يسار مولى ميمونة بنت الحارث (Sunan Abi Dawud)
The Prophet (ﷺ) said: When a man goes into his house, he should say: “O Allah! I ask Thee for good both when entering and when going out; in the name of Allah we have entered, and in the name of Allah we have gone out, and in Allah our Lord do we trust.” He should then greet his family.
Grade: Da'if

Hadith #5141 - Sunan Abi Dawud - Abdullah bin Dinar عبد الله بن دينار العدوي; Ahmed bin Manay' أحمد بن منيع; al-Laith bin Sa'd الليث بن سعد; Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; ibn Umar (Sunan Abi Dawud)
A man’s reviling of his parents is one of the grave sins. He was asked : Messenger of Allah! How does a man revile his parents? He replied: He reviles the father of a man who then reviles his father, and he reviles a man’s mother and he reviles his.
Grade: Sahih